Exertional Angina Due To Fused Aortic Bioprosthesis During Left Ventricular Assist Device Support: Two Cases and Review of the Literature. Issue 1 (January 2017) - Bonios, Michael J.; Selzman, Craig H.; Gilbert, Edward M.; McKellar, Stephen H.; Koliopoulou, Antigoni; Strege, Jennifer L.; Nativi, Jose N.; Fang, James C.; Stehlik, Josef; Drakos, Stavros G.
Abstract : We present the case of two patients with idiopathic dilated cardiomyopathy and moderate aortic valve regurgitation that were treated with a bioprosthetic valve at the time of the left ventricular assist device (LVAD) implantation. A few months later, patients revealed partial recovery in the left ventricle systolic function. Both patients, during the LVAD turndown protocol, reported the onset of chest pain. The transthoracic echocardiography revealed the presence of a new transaortic pressure gradient. We confirmed the presence of a fused bioprosthetic valve by further performing a transesophageal echocardiogram and a left and right heart catheterization. Replacement of aortic valve at the time of an LVAD implantation constitutes a challenging case. Although a mechanical valve is contraindicated due to the increased thromboembolic risk, selecting a bioprosthetic valve increases the risk of valve leaflets fusion. The consequences of this phenomenon should be acknowledged in LVAD patients undergoing aortic valve replacement with a bioprosthetic, especially under the view of LVAD explantation for those revealing myocardial recovery under mechanical unloading.